1998
DOI: 10.1029/1998gl900046
|View full text |Cite
|
Sign up to set email alerts
|

Ozone formation in biomass burning plumes: Influence of atmospheric dilution

Abstract: Abstract. Biomass burning in the tropics contributes substantially to the emission of organic compounds and nitrogen oxides into the troposphere and has an important impact on the global budget of ozone in the troposphere. Since ozone formation is a nonlinear chemical process the rate of formation is also influenced by atmospheric dilution and transport. This paper addresses the production of ozone in a plume emerging from a biomass burning site. Atmospheric mixing processes downwind the fire are expected to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 10 publications
0
50
0
Order By: Relevance
“…However, the amount of ozone produced per NO x emitted is not linear (Liu et al, 1987;Lin et al, 1988;Trainer et al, 1993). With NO x ozone production increases at high NO x levels and decreases at high NO x levels, and the NO x threshold is around 1-10 ppbv, depending on NMVOC conditions and so on (Poppe et al, 1998). Generally, surface NO x levels in polluted areas of eastern China fall in this range (Fig.…”
Section: Ozone Concentrationsmentioning
confidence: 97%
“…However, the amount of ozone produced per NO x emitted is not linear (Liu et al, 1987;Lin et al, 1988;Trainer et al, 1993). With NO x ozone production increases at high NO x levels and decreases at high NO x levels, and the NO x threshold is around 1-10 ppbv, depending on NMVOC conditions and so on (Poppe et al, 1998). Generally, surface NO x levels in polluted areas of eastern China fall in this range (Fig.…”
Section: Ozone Concentrationsmentioning
confidence: 97%
“…For example, the ozone production efficiency N , defined as the ratio of ozone molecules produced per nitrogen oxide (NO x =NO+NO 2 ) molecule destroyed (Lui et al, 1987;Lin et al, 1988) is known to increase with the rate that NO x emissions are mixed into the environment (Chatfield and Delaney, 1990;Jacob et al, 1993;Poppe et al, 1998). Esler et al (2001) have demonstrated that hydroxyl radical (OH) levels are sensitive to mixing between tropospheric and stratospheric air.…”
Section: Introductionmentioning
confidence: 99%
“…However, Liousse et al (1996) in their global model studies of carbonaceous aerosols, showed that the predicted concentrations in remote areas are extremely dependent on the height of injection of the aerosols, among others factors. Chatfield and Delany (1990) and Poppe et al (1998) demonstrated that due to the nonlinearity of ozone production, the rate of ozone formation is influenced by atmospheric dilution and transport. Consequently, the plume rise mechanism plays an important role.…”
Section: Introductionmentioning
confidence: 99%